2016
DOI: 10.4028/www.scientific.net/msf.869.890
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatites Obtained from Different Routes and their Antimicrobial Properties

Abstract: Among applications of ceramics in technological context, hydroxyapatite (HAp) stands out in the scientific community due to chemical biocompatibility and molecular similarity with the structures of bone and dental tissues. Such features are in addition to its antimicrobial properties. This work aimed firstly to synthesize hydroxyapatite by two different routes: hydrothermal (HD HAp) and co-precipitation (CP HAp), and secondly to verify the antimicrobial properties of these materials through direct contact test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…Therefore, it is crucial to determine the antibacterial properties of biomaterials, especially against E Coli and S Aureus bacteria because these are the most common sources of contamination in implants. 11 In recent years, different studies prepared natural HA from different biological sources, eg pig bone, pig teeth, human teeth at different sintering temperatures and using wet chemical precipitation method where the sintering temperature was controlled with a soaking time of 4 hours to study the phase evolution of the single phase HA to biphasic HA/β-TCP. 12,13 These works used different sources to investigate the effect of sintering temperature on the properties of HA.…”
mentioning
confidence: 99%
“…Therefore, it is crucial to determine the antibacterial properties of biomaterials, especially against E Coli and S Aureus bacteria because these are the most common sources of contamination in implants. 11 In recent years, different studies prepared natural HA from different biological sources, eg pig bone, pig teeth, human teeth at different sintering temperatures and using wet chemical precipitation method where the sintering temperature was controlled with a soaking time of 4 hours to study the phase evolution of the single phase HA to biphasic HA/β-TCP. 12,13 These works used different sources to investigate the effect of sintering temperature on the properties of HA.…”
mentioning
confidence: 99%
“…The antibacterial activity observed for hydroxyapatite against S. aureus may be associated with the hydrophilic nature of this material due to the presence of hydroxyl groups, which may favor the interaction with the cell wall of Gram-positive bacteria (Feitosa et al 2016). The antimicrobial activity of hydroxyapatite can be attributed to the production of reactive oxygen species (OH − , H 2 O 2 , and O 2 −2 ) on the surface of the hydroxyapatite nanoparticles, linked with fatal damage to the bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The physico-chemical and, consequently, antimicrobial properties of hydroxyapatite can be affected by synthesis conditions, namely reagent addition rate, reaction temperature, and others (Koutsopoulos 2002; Janusz and Skwarek 2009; Kehoe et al 2011). Hydroxyapatite is commonly prepared by wet precipitation (Monmaturapoj 2008; Abidi and Murtaza 2014; Feitosa et al 2016), sol–gel (Sanosh et al 2009; Costescu et al 2010; Agrawal et al 2011), and hydrothermal method (Earl et al 2006; Feitosa et al 2016). However, the use of calcination (Mkukuma et al 2004; Figueiredo et al 2010; Fara and Abdullah 2016) and chemical treatment to obtain hydroxyapatite (Barakat et al 2008) has also been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It presents a three-dimensional (3D) hierarchical structure compound by cells, non-collagenous proteins, hyaluronan, peptoglycans and nanocollagen fibers mineralized with hydroxyapatite (HA). HA, in particular, is the major bio-calcium hydroxyapatite (HA), Ca10(PO4)6(OH)2; alphaor beta-tricalcium phosphate (α-or β-TCP), Ca3(PO4)2; biphasic calcium phosphates (BCPs) for mixtures of HA and β-TCP; and unsintered apatites or calcium-deficient apatites (CDAs) [24][25][26][27][28] . Solubility and biological properties of those materials are extremely dependent on crystal size, ionic impurities, specific surface area, and both macroporosity and microporosity.…”
Section: -12mentioning
confidence: 99%